Estrutura de vidros fosfatos ternários no sistema Pb-Al metafosfato - Tsuchida, Jefferson Esquina (2008)
In this work, the Pb-Al meta-phosphate glass system (1-x) Pb(PO3)2 xAl(PO3)3 was studied, with the aim of determining the structural effects induced in the glass network by the substitution of Pb by Al. In the series of glasses encompassing the range 0 ≤ x ≤ 1 the composition meta [O/P] = 3 was maintained. In this way, the resulting phosphate network will be composed mainly by phosphate tetrahedra in condensation Q2 (chains or rings), simplifying the formulation of structural models. The structure of this system was analyzed trough a combination of Raman spectroscopy and Nuclear Magnetic Resonance (NMR). The structural environments around the network former and modifiers species were analyzed by 31P, 27Al and 207Pb-NMR, quantifying the distribution of phosphate groups and determining the coordination numbers of Al and Pb. For phosphate groups, several Q2 species were identified according to the number of P-O-Pb and P-O-Al bonds established by each tetrahedron. Through the quantitative analysis of the evolution of the population of these species with the concentration of Al, it was possible to infer specific characteristics of organization of the Al coordination polyhedra and phosphate tetrahedra. Phosphates share preferentially only a single corner with an Al-O polyhedron, which is found with high coordination number, and the other corner with a Pb-polyhedron. As x is increased, this medium range arrangement around Al is maintained through the progressive decrease of the Al coordination number, up to a certain critical concentration (x = 0.43). Above this concentration, the arrangement is not sustained and phosphates sharing two corners with Al-polyhedrons appear. On the other hand, the environments around Pb have high coordination numbers and a considerable degree of cornersharing between Pb-polyhedra was determined. The dependence of Pb coordination number with composition is determined by the quantity of available Onp, without apparent modification in the degree of O-sharing. The behavior observed for the local order around the Al and the arrangement of coordination polyhedra is similar to the observed in tow other meta-phosphates (Ca-Al and Na-Al), pointing out to a possible general trend for ternary phosphate glasses.